2020
DOI: 10.1039/c9ta12494b
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube yarn based thermoelectric textiles for harvesting thermal energy and powering electronics

Abstract: Wearable thermoelectric devices show promises to generate electricity in a ubiquitous, unintermittent and noiseless way for on-body applications. Threedimensional thermoelectric textiles (TETs) outperform other types in smart textiles owing to their out-of-plane thermoelectric generation and good structural conformability with fabrics. Yet, there has been lack of efficient strategies in scalable manufacture of TETs for sustainably powering electronics. Here, we fabricate organic spacer fabric shaped TETs by kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
115
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 77 publications
1
115
1
Order By: Relevance
“…ZT for the films is calculated by assuming that the thermal conductivities of the PEI doped films remain constant as the concentration varies from 5 to 20 wt.% PEI. 3 SWCNT-PEI, 4 SWCNT, 4 MWCNT-PEI, 5 and MWCNT-PEDOT:PSS. 5 This work (indicated by ) shows high PF with lower κ than other reported materials.…”
mentioning
confidence: 99%
“…ZT for the films is calculated by assuming that the thermal conductivities of the PEI doped films remain constant as the concentration varies from 5 to 20 wt.% PEI. 3 SWCNT-PEI, 4 SWCNT, 4 MWCNT-PEI, 5 and MWCNT-PEDOT:PSS. 5 This work (indicated by ) shows high PF with lower κ than other reported materials.…”
mentioning
confidence: 99%
“…This was attributed to the dipole moments arising from both the ethylamine molecule from PEI as well as the ethylamine/CNT interface dipole as the PEI is physisorbed onto the outer layers of the MWCNTs [232]. These yarns were then knitted into a 3D fabric with a spacer in between, creating the TET with a maximum power output of 51.5 mW/m 2 at an applied temperature gradient of 47.5 K [6]. At the fabric level, Yu et al used vacuum [81].…”
Section: Carbon-based Thermoelectric Materialsmentioning
confidence: 99%
“…Textiles provide an accessible platform for the deployment of TEC devices due to the conformal and intimate contact they make with the body. Additionally, the hierarchical nature of fabrics as they progress from fiber to yarn to fabric allows the integration of TEC modules directly into the woven structure, thereby creating a more seamless fabric-based TEC device [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to pure CNT, Kim et al reported SWCNT/poly (vinylidene fluoride) (PVDF) composite fibers with p-and n-type power factors of 378 ± 56 and 298 ± 98 µW m −1 K −2 respectively 16 . Recently, Zheng et al designed three-dimensional thermoelectric textiles (TETs) with a high output power density of 51.5 mWm −2 and a high specific power of 171.7 µW(gK) −1 at ∆T = 47.5 K 17 . Despite high power factor, all these reports are based on CNT yarn composed of SWCNTs or DWCNTs 9,13,[15][16][17] , which require precise control in fabrication process, and hence incurring high cost for mass production.…”
mentioning
confidence: 99%
“…Recently, Zheng et al designed three-dimensional thermoelectric textiles (TETs) with a high output power density of 51.5 mWm −2 and a high specific power of 171.7 µW(gK) −1 at ∆T = 47.5 K 17 . Despite high power factor, all these reports are based on CNT yarn composed of SWCNTs or DWCNTs 9,13,[15][16][17] , which require precise control in fabrication process, and hence incurring high cost for mass production. Therefore, the application of CNT yarn made of few-walled CNTs (FWCNTs) in TE generators is more attractive to explore, compared to that of SWCNTs or DWCNTs, owing to low fabrication cost and availability of large quantity.…”
mentioning
confidence: 99%